Anxiolytic Effect Of Ethanolic Extract Of Oxalis Corniculata .L In Mice - SAI SAMPATH. T; SANTOSH.P; MANGALA LAHKAR; AJAYGODWIN.P; PAVAN KUMAR.S; LINGESH.A. (International Journal of Pharma and Bio Sciences, 2011)
The aim of the study is to evaluate anxiolytic effect of Ethanolic extract of Oxalis corniculata (200mg/kg and 400mg/kg P.O) on male mice using various paradigms of anxiety. In elevated plus maze, extract ( 200mg/kg and 400mg/kg) had shown a dose-dependent increase in time spent and number of entries into open arm compared to control group. The number of central squares, peripheral squares crossed and rearings were stepped up significantly in open field paradigm. The treated groups had shown accession in time spent in light compartment, number of crossings, latency compared to control group in light dark exploration test. In Hole board model, number of head dips were minified in mice that received Ethanolic extract of Oxalis corniculata (200mg/kg and 400mg/kg). Further studies are required to find out the exact chemical constituent and mechanism responsible for anxiolytic effect.